Pedagogical practices with differential approach at Sena and augmentative and alternative communication - Galindo Bejarano, Leonor
Augmentative and alternative communication is a work and interdisciplinary investigation field relatively recent in Colombia (90’s), which objective is oriented to make possible other ways of communication different to the oral to those people that for different reasons find that process difficult or impossible to perform such process. The importance of this field and its possibilities on the development of one of those human dimensions as it is communication, this is one of the main reasons that determined that a teaching team from the National Pedagogical University in 2019 took the decision to undergo a research on this field, barely explored in our means regarding the existent steps around the same and its use, both in educative and family fields. The current document aims to show the possible articulation of the results of that research, with the pedagogical practices with applied differential approach in the Integral Professional Formation (IPF) at SENA, as long as one of the axis that this policy starts on the Resolution 1726 (SENA, 2014) is the human talent management of the institution regarding to its qualification on this sense. Besides, within the missional processes mentioned by the resolution we find: “to create and strength learning environments for the attention with differential approach within the principle of design for everyone”, mission that can be addressed from this interdisciplinary field, which has a wide theoretical production, some intervention strategies, some sign systems and technical aids that contribute with the achievement of this purpose, in proportion with the use of other languages different to the oral in the pedagogical practices, as well as the uses and representations that are done from it in the Colombian context, which can lead to the way that the formation programs can be set and enrich the pedagogical practices from the reality that about this topic is seen in our environment. For this, it was defined as a main objective to systematize experiences of conceptions and everyday uses of the augmentative and alternative communication of teachers, relatives and disabled people.